2022
DOI: 10.3390/ani12233398
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Analysis of Transcriptomic and Metabolomics Profiles Reveal the Molecular Regulatory Network of Marbling in Early Castrated Holstein Steers

Abstract: The intramuscular fat (IMF), or so-called marbling, is known as potential determinant of the high quality beef in China, Korea, and Japan. Of the methods that affect IMF content in cattle, castration is markedly regarded as an effective and economical way to improve the deposition of IMF but with little attention to its multi-omics in early-castrated cattle. The aim of this study was to investigate the liver transcriptome and metabolome of early-castrated Holstein cattle and conduct a comprehensive analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Higher levels of tricarboxylic acid (TCA) cycle (cis-aconitic acid, citric acid, isocitric acid), lipid synthesis (3-hydroxybutiric acid, glycerol 3-phosphate), FA metabolism (o-acetylcarnitine), diabetes (methylhistidine, asymmetric dimethylarginine), and glucose homeostasis (hippuric acid) were found for blood metabolme in Wagyu cattle compared to Holstein [ 46 ]. Early castration of Holstein calves was shown to improve beef marbling grade [ 47 ]. Untargeted metabolomics analysis of the liver showed that the early castration group had increased betaine, glycerol 3-phosphate, glutathione, acetylcarnitine, riboflavin, and alanine and decreased diethanolamine, glycine, and 2-hydroxyglutarate, which were associated with the increased marbling [ 47 ].…”
Section: Host and Microbial Metabolome Contribution To Beef Meat Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Higher levels of tricarboxylic acid (TCA) cycle (cis-aconitic acid, citric acid, isocitric acid), lipid synthesis (3-hydroxybutiric acid, glycerol 3-phosphate), FA metabolism (o-acetylcarnitine), diabetes (methylhistidine, asymmetric dimethylarginine), and glucose homeostasis (hippuric acid) were found for blood metabolme in Wagyu cattle compared to Holstein [ 46 ]. Early castration of Holstein calves was shown to improve beef marbling grade [ 47 ]. Untargeted metabolomics analysis of the liver showed that the early castration group had increased betaine, glycerol 3-phosphate, glutathione, acetylcarnitine, riboflavin, and alanine and decreased diethanolamine, glycine, and 2-hydroxyglutarate, which were associated with the increased marbling [ 47 ].…”
Section: Host and Microbial Metabolome Contribution To Beef Meat Qualitymentioning
confidence: 99%
“…Early castration of Holstein calves was shown to improve beef marbling grade [ 47 ]. Untargeted metabolomics analysis of the liver showed that the early castration group had increased betaine, glycerol 3-phosphate, glutathione, acetylcarnitine, riboflavin, and alanine and decreased diethanolamine, glycine, and 2-hydroxyglutarate, which were associated with the increased marbling [ 47 ]. The above findings suggest that both host and microbial metabolites could play a role in affecting meat quality.…”
Section: Host and Microbial Metabolome Contribution To Beef Meat Qualitymentioning
confidence: 99%
“…Currently, in the cattle breeding industry, there are many management difficulties with pain and distress on the animals. Thus, using castration techniques to improve animal interest benefits the said industry (8). The intracellular antioxidant levels decreased in the chemical-castrated animals by elevating reactive oxygen species (ROS) levels.…”
Section: Introductionmentioning
confidence: 99%